Civil engineering in the nuclear industry proceedings of the conference organized by the Institution of Civil Engineers and held in Windermere on 20-22 March 1991 - Dexter-Smith, R. (Thomas Telford, 1991)
Civil engineering has an important part to play at every stage of the nuclear fuel cycle. This book examines ways in which the industry has responded to this challenge with new methods of construction giving higher productivity and faster construction times.